2021
DOI: 10.2147/dmso.s285025
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rooibos (Aspalathus linearis), Honeybush (Cyclopia intermedia) and Sutherlandia (Lessertia frutescens) on Testicular Insulin Signalling in Streptozotocin-Induced Diabetes in Wistar Rats

Abstract: Background: Testicular insulin signalling is altered in diabetic (DM) males. While unravelling the mechanism through which DM exert these detrimental effects, studies have shown the importance of insulin regulation in glucose homeostasis, and how a lack in insulin secretion indirectly led to reduced male fertility. The current study aimed to investigate the role of rooibos, honeybush and Sutherlandia on insulin signalling in the testicular tissue of type I diabetic rats. Methods: Animals (n=60) were randomly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Several other studies have also revealed a significant decrease in semen volume, sperm motility and morphology in the semen of diabetic men ( 148 , 149 ) while some animal studies have equally reported alteration in sperm parameters ( 150 152 ). All these effects can partly be explained through the impact of OS, caused by the inequality between ROS production and antioxidant defense mechanisms ( Figure 5 ) ( 19 , 153 ). The process of how OS leads to male subfertility or infertility has been discussed in detail in the earlier section.…”
Section: Diabetes Mellitus-induced Os In Male Infertilitymentioning
confidence: 99%
“…Several other studies have also revealed a significant decrease in semen volume, sperm motility and morphology in the semen of diabetic men ( 148 , 149 ) while some animal studies have equally reported alteration in sperm parameters ( 150 152 ). All these effects can partly be explained through the impact of OS, caused by the inequality between ROS production and antioxidant defense mechanisms ( Figure 5 ) ( 19 , 153 ). The process of how OS leads to male subfertility or infertility has been discussed in detail in the earlier section.…”
Section: Diabetes Mellitus-induced Os In Male Infertilitymentioning
confidence: 99%
“…After three weeks, the rats subjected to a single intra-peritoneal injection of 45 mg/kg of freshly prepared streptozotocin dissolved in 0.1 M citrate buffer. Besides, to avoid animal death, 20 percent glucose was added to the drinking water for 48 h after induction with the intra-peritoneal streptozotocin injection [ 57 , 58 ]. At 72 h after streptozotocin induction, diabetic rats were defined as those with blood glucose levels greater than 300 mg/dL as determined by a blood sample from the rat’s tail using an (ACCU-CHEK ® , Roche, Hague Road, Indianapolis, IN, USA) instrument [ 59 ].…”
Section: Methodsmentioning
confidence: 99%
“…Compared with fermented rooibos, unfermented rooibos possesses a higher level of aspalathin (Canda et al, 2014; Kwak et al, 2015). Aspalathus linearis reduced testosterone production in TM3 Leydig cells (Opuwari & Monsees, 2015) and diabetic male rats (Omolaoye et al, 2021). In other studies, A. linearis improved male reproductive functions in rat models (Awoniyi et al, 2012; Opuwari & Monsees, 2014).…”
Section: Introductionmentioning
confidence: 99%